2019
DOI: 10.1111/bdi.12789
|View full text |Cite
|
Sign up to set email alerts
|

Psychotic symptoms and suicidal ideation in child and adolescent bipolar I disorder

Abstract: Objectives:The purpose of this study was to explore associations between specific types of hallucinations and delusions and suicidal ideation in a sample of children and adolescents with bipolar I disorder. Methods: Participants (N = 379) were children and adolescents aged 6-15 years (M = 10.2, SD = 2.7) with DSM-IV diagnoses of bipolar I disorder, mixed or manic phase. The study sample was 53.8% female and primarily White (73.6% White, 17.9% Black, and 8.5% Other). Presence and nature of psychotic symptoms, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…For instance, the investigation of variables associated with distinct outcomes in children and adolescents with BD may allow the identification of features indicating the need for specific interventions. Duffy et al (9) found that a history of hallucinations, delusions of guilt, and many different psychotic symptoms were associated with suicidal ideation in young patients with BD type I (9). Suicide risk in children and adolescents with BD was also associated with sleep disorders in the study of Stanley et al (10).…”
Section: Introductionmentioning
confidence: 98%
“…For instance, the investigation of variables associated with distinct outcomes in children and adolescents with BD may allow the identification of features indicating the need for specific interventions. Duffy et al (9) found that a history of hallucinations, delusions of guilt, and many different psychotic symptoms were associated with suicidal ideation in young patients with BD type I (9). Suicide risk in children and adolescents with BD was also associated with sleep disorders in the study of Stanley et al (10).…”
Section: Introductionmentioning
confidence: 98%